The Utilization of Watermelon Peel Flour in Making Traditional Nagasari Cakes - Dwiputri, Alya Syabila (Journal Research of Social Science, Economics, and Management, 2025)
Watermelon (Citrullus lanatus) is advantageous because it can be cultivated year-round. However, data from the Central Statistics Agency of Riau Islands Province (2025) show that its production has fluctuated over the years. This research aims to utilize watermelon peel as a substitute for rice flour in making traditional nagasari cakes. The innovation addresses the high percentage of wasted watermelon peels, which can cause environmental pollution. The study used an experimental method with a Complete Randomized Design (RAL) and three substitution levels of watermelon peel flour: 25%, 50%, and 75%. The peels were dried at 60°C for 9–10 hours, then ground and sifted into fine flour. The resulting nagasari products were evaluated organoleptically by 20 panelists using hedonic and hedonic quality tests. Results showed that increasing the substitution level significantly affected color, producing a darker appearance due to the Maillard reaction. In contrast, no significant differences were found in aroma and taste among the formulas. However, texture varied, with higher substitution producing softer cakes. The 25% substitution formula (sample 173) received the highest rating from panelists. Therefore, using watermelon peel flour in nagasari production supports food diversification while offering an innovative approach to reducing organic waste, consistent with zero-waste and sustainable food principles.